Assembly of silica aerogels within silica nanofibers: towards a super-insulating flexible hybrid aerogel membrane. Issue 111 (27th October 2015) - Zheng, Hongxia; Shan, Haoru; Bai, Ying; Wang, Xianfeng; Liu, Lifang; Yu, Jianyong; Ding, Bin
Abstract : A robust flexible hybrid aerogel membrane with super-insulating properties and improved mechanical properties is developed by forming an interpenetrating silica nanoparticle network inside an electrospun silica nanofibrous scaffold. Abstract : Silica aerogels (SA) have well been recognized as one of the most attractive thermal insulation materials, but the inherent brittleness and moisture sensitivity hinder wide applications of these materials. Here, we report the design and fabrication of robust flexible hybrid silica nanofiber (SNF)–SA membranes with super-insulating properties and improved mechanical properties by formation of an interpenetrating network of mesoporous silica within a flexible SNF scaffold. The hybrid SNF/SA membranes were obtained by impregnating electrospun SNF membranes with silica sol, then aging, solvent exchanging, surface modification, and drying at ambient atmosphere. The resultant highly porous (>90%) hybrid SNF/SA membranes exhibit meso- and macroporosity with average pore diameter less than free path of air molecules, improved mechanical strength (224% increase in tensile strength), good flexibility (stiffness < 337.6 mN), hydrophobicity (water contact angle > 144.2°), while maintaining low thermal conductivity (0.021 W m −1 K −1 under ambient conditions). Such a robust hybrid membrane with remarkable integrated performance will have great potential in special thermal management applications under harsh conditions, such as the aerospace field. This success of interpenetrating porous SA in inorganic nanofibrous scaffolds paves a new avenue for the synthesis of multifunctional hybrid aerogels.